Wogonin Attenuates Isoprenaline-Induced Myocardial Hypertrophy in Mice by Suppressing the PI3K/Akt Pathway - Qian, Weichun; Yu, Dongsheng; Zhang, Jia; Hu, Qiaoyun; Tang, Chuanfeng; Liu, Peiyu; Ye, Peng; Wang, Xiaoli; Lv, Qiu; Chen, Minglong; Sheng, Liang (Frontiers in Pharmacology, 2018)
Many studies have focused on identifying therapeutic targets of myocardial hypertrophy for the treatment of multiple cardiac events. Wogonin is a natural flavonoid compound that displays a potent anti-hypertrophic effect. Knowledge of its pharmacological mechanisms might reveal an effective way to search for therapeutic targets. Myocardial hypertrophy was replicated by the subcutaneous implantation of an isoprenaline mini-pump in mice or isoprenaline treatment of H9C2 cells. Pathologic changes in cardiac structure were assessed by echocardiographic and histological examinations. The signaling transductions in hypertrophy-promoting pathways and the genes involved were detected by western blot and RT-qPCR. Wogonin significantly attenuated isoprenaline-induced myocardial hypertrophy in vivo and in vitro by suppressing phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) hypertrophy-promoting pathway. Wogonin promoted the ubiquitination and degradation of PI3K catalytic subunit alpha (Pik3ca), the catalytic subunit of PI3K, which was upregulated by isoprenaline treatment. Wogonin also increased the expression of neural precursor cells expressing developmentally down-regulated gene 4-like (Nedd4l), the ubiquitin E3 ligase of Pik3ca. Therefore, wogonin targets Nedd4l to induce the degradation of Pik3ca, which reverses the over-activation of the PI3K/Akt pathway, and finally releases the isoprenaline-induced myocardial hypertrophy.